ESTIMATION OF PROFIT FUNCTION OF WHEAT CROP IN DHI QAR PROVINCE - &et al., Barbaz (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research aims to study the most important factors affecting profit function. Cross sectional data were used in the light of a random sample of 130 farmers in Dhi Qar province. The results showed that the proportion of costs of production inputs amounted to 73% of the total production costs. Also, profit function showed that the amount of output has a significant impact on profit compared to other independent variables since value of the parameter of the quantity of production amounted to about 308879 and was significant at the level of 1% according to t-test. The coefficient determination of about 93% for the equation estimated with OLS. However, heteroscedasticity was obvious according to the White Test. So the model was estimated using robust regression method to avoid this problem, but that led to a decrease in R2 to about 69%. The research recommended the need to increase the rates of production growth and productivity through an organized agricultural economic policy that links the policy of supporting input requirements, both in terms of reducing prices or providing quantity and quality, especially fertilizers and seeds in conjunction with the policy of supporting prices of output. Also, research recommended encouraging farmers to expand wheat crop cultivation in the province of Dhi Qar by increasing the cultivated areas.